Analisis Perilaku Konsumen Dalam Pembelian Kopi Luwak - Deni Setiawan; Harun Al Rasyid; Wisnu Satyajaya (Inovasi Pembangunan : Jurnal Kelitbangan, 2015)
This study was aimed to identify the decision process,which was carried out by the consumer in buying civet coffee drinks, Analyzing the level of consumer satisfaction of civet coffee, and getting the alternative policy of marketing based on the study of consumer behavior to civet coffee marketing of Duta Luwak Brothers Link company. The Analysis conducted using descriptive analysis, the ideal point model, the Index Performance Analysis (IPA),and Customer Satisfaction Index (CSI). The results showed that the most considered attribute when buying a civet coffee was quality product which equal to 22%.Beside that, 44% of Duta Luwak Brothers Link’s consumers have been loyal because they bought civet coffee planned. The results of analysis multiattribute ideal number was 17.3,which means Index Performance Analysis (IPA) indicated that the attribute of Duta Luwak Civet Coffee Brothers Link which deemed less satisfied customers was advertising and promotion. Results of Customer Satisfaction Index (CSI) reached 77.76% with the interval of 0.66 to 0.80. Suggestion for marketing policy of Duta Luwak Brothers Link is to improve the quality of civet coffee products. In term of price, this company should be reconsider the pricing strategy of civet coffee.